One-step synthesis of epoxy/cyclic carbonate bifunctional polycarbonates with functional groups - Jie Huang; Boxiong Shen (Carbon Capture Science & Technology)
The synthesis of functionalized polycarbonates from CO2 has gained significant attention due to their versatile properties and potential in high-performance applications. A novel trinuclear tetradentate Schiff base chromium complex 1 was designed and synthesized, and combined with bis(triphenylphosphine) imidazolium salt (PPNN3) to form a binary catalytic system (complex 1/PPNN3). This system was employed to catalyze the copolymerization of CO2 with bicyclic epoxide compounds containing both terminal and internal epoxy groups (VCHDEP). Experimental results demonstrate that a bifunctional polycarbonate (PVCH) was efficiently synthesized through a simple one-step process, featuring a polycarbonate cyclohexene ester backbone with side chains containing both epoxy (EP) and cyclic carbonate (CC) groups. The EP/CC ratio can be precisely tuned by varying the reaction temperature and the molar ratio of PPNN3, enabling control over polymer properties. Notably, the glass transition temperature (Tg) of PVCH was found to be 164.5 °C, significantly higher than that of conventional polycarbonates synthesized from bisphenol A (154 °C), indicating superior thermal stability and mechanical robustness. The complex 1/PPNN3 catalytic system selectively catalyzed the ring-opening copolymerization of epoxides to form the polymer backbone, while retaining unreacted epoxy groups in the side chains. In this catalytic system, the enthalpy change (ΔHₚθ) for the VCHDEP ring-opening polymerization is -20.5 kJ mol-1, the entropy change (ΔSₚθ) is -80.3 J mol-1 K-1, the Gibbs free energy change (ΔGₚθ) is 3.5 kJ mol-1, and the activation energy (Ea) for PVCH synthesis is 56.8 kJ/mol. Furthermore, hydrolysis and amination reactions were performed on the cyclic carbonate and epoxy groups in PVCH, yielding polycarbonates with hydroxyl, amide, and other functional groups, which further enhance the material's versatility for applications requiring strong adhesion, biocompatibility, and chemical reactivity. This work not only demonstrates a highly efficient and selective catalytic system but also provides a strategy for expanding the application potential of CO2-based polycarbonates in advanced materials.